ATELIERS PHILO DANS UN COLLÈGE REP : LE QUESTIONNEMENT ET LA COMMUNAUTÉ DE RECHERCHE COMME FIL ROUGE PÉDAGOGIQUE - BLANC-LANAUTE, Chrystelle; LEDIEU, Maxime (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
Philosophy Workshops in a REP College: Questioning and the Community of Inquiry as a Pedagogical Common Thread. We describe in this paper the philosophy workshops implemented in a secondary school in Grenoble. We present some of the materials we use. We describe the effects of this project on the children and especially on the teachers. The teachers taking part in the project have entered into a process of questioning more generally their own teaching pratices: which activities in other academic subjects could be based on the community of philosophical enquiry’s dynamic of questioning, exploring, researching? Which other models of community of enquiry might we imagine (litterary, grammatical, scientific, historical)?